Abbreviations Used By Millennials on Instagram: A Morphosemantic Study - Ruth Sherly Mitha Uli Grace; Heri Heryono (Ethical Lingua: Journal of Language Teaching and Literature, 2022)
This thesis is entitled “Abbreviations Used by Millennial on Instagram Morpho-semantic Studies”. The purpose of this research is to analyze the types and meanings of abbreviations contained in captions and comments on Instagram. The research method used in this study is a descriptive method to analyze the types of abbreviations on Instagram. The steps taken in this research are to collect data in the form of sentences that have abbreviations founded on Instagram, then analyze the types of abbreviations in captions and comments on Instagram. The theoretical basis used in this research is the theory of Verhaar (1993) in analyzing the types of abbreviations and the theory of Griffith (2006) to analyze the types of meaning. From the results obtained in this study, it shows that the 30 of data that has been analyzed, there are 4 (13,3%) acronyms data, 16 (56,6%) initializes data, 4 (13,3%) blending data, 4 (13,3%) clipping data and 2 (6,6%) compounding data. Meanwhile, the type of meaning that has been founded included is 30 data (100%).